PAK-dependent STAT5 serine phosphorylation is required for BCR-ABL-induced leukemogenesis - Berger, Angelika; Hoelbl-Kovacic, A.; Bourgeais, J.; Hoefling, L.; Warsch, W.; Grundschober, E.; Uras, I. Z.; Menzl, I.; Putz, E. M.; Hoermann, G.; Schuster, Christoph M.; Fajmann, S.; et al. (Leukemia, 2014)
The transcription factor STAT5 (signal transducer and activator of transcription 5) is frequently activated in hematological malignancies and represents an essential signaling node downstream of the BCR-ABL oncogene. STAT5 can be phosphorylated at three positions, on a tyrosine and on the two serines S725 and S779. We have investigated the importance of STAT5 serine phosphorylation for BCR-ABL-induced leukemogenesis. In cultured bone marrow cells, expression of a STAT5 mutant lacking the S725 and S779 phosphorylation sites (STAT5SASA) prohibits transformation and induces apoptosis. Accordingly, STAT5SASA BCR-ABL+ cells display a strongly reduced leukemic potential in vivo, predominantly caused by loss of S779 phosphorylation that prevents the nuclear translocation of STAT5. Three distinct lines of evidence indicate that S779 is phosphorylated by group I p21-activated kinase (PAK). We show further that PAK-dependent serine phosphorylation of STAT5 is unaffected by BCR-ABL tyrosine kinase inhibitor treatment. Interfering with STAT5 phosphorylation could thus be a novel therapeutic approach to target BCR-ABL-induced malignancies.
advance online publication,13 December 2013
Gesehen am 23.11.2020